Lung Protective Strategy in Acute Respiratory Distress Syndrome with Approach of Compliance and Mechanical Power - Pamugar, Bramantyo; Budipratama, Dhany (CoinReads Media Prima, 2023)
Introduction: Lung protective strategy was meant to decrese risk of ventilatory induced lung injury without reducing benefit of ventilator. One of the approaches were the use of compliance and mechanical power (MP). Compliance was used to determine how large lung was recruited after ventilatory support. Mechanical power was used to determined enough ventilatory support to that patient. Case Report: We reported 36 years old female, whom admitted to ICU with diagnosis of acute respiratory distress syndrome caused by community acquired pneumonia. Patient was given pressure controlled ventilation with driving pressure 15cmH2O, positive end expiratory pressure (PEEP) 5 cmH2O, respiratory rate of 20x/min. We used compliance and MP to decide ventilator setting which benefit the patient. At the initial ventilator setting compliance and MP were 15.67 cc/mmHg, and 9.21 joule/min respectedly. The PEEP was increase gradually to 12 cmH2O. Compliance and MP were also increase to 41.67 cc/mmHg and 32.91 joule/min respectedly. Driving pressure was decrease to meet desirable volume tidal 6cc/kg and desirable MP below 22 joule/min. The PEEP was maintained until pneumonia resolved. Patient was extubated in ninth day. Conclusion: It could be concluded that the use of compliance and MP would help customize ventilatory support the patient need. They would help critical care clinician in making decision to prioritize need of ventilatory support in each individual patient.